Is Personal Branding pushing the epistemological boundaries of marketing? - Zarkada, Anna K. (My University, 2014)
Personal branding, a fast-growing body of popular literature, is so far ignored or scorned by academics. Utilising discourse analysis, this paper reviews definitions of personal branding, identifies the epistemological issues they raise and highlights the inconsistencies that point towards its interpretation as a frantic attempt by marketers to expand the market for their services. It re-defines the concept and positions it within the service-dominant logic of marketing and the corporate branding literature thus relieving the tensions caused by the productbased orientation of the extant literature. The value of the work lies in the positioning of personal branding as an analytical tool for understanding people as the common ground between theory and practice. It suggested that the time is ripe for marketing scholars to re-examine both themselves and the role of marketing as a tool for satisfying the emotional needs of people living in a world of flux.
Keywords: personal branding; discourse analysis; corporate branding theory; literature review; conceptual model; service-dominant logic